Uso do regulador de crescimento etil-trinexapac em arroz de terras altas - Nascimento, Vagner do [UNESP]; Arf, Orivaldo [UNESP]; Silva, Matheus Gustavo da [UNESP]; Binotti, Flávio Ferreira da Silva [UNESP]; Rodrigues, Ricardo Antonio Ferreira [UNESP]; Alvarez, Rita de Cássia Felix (FapUNIFESP (SciELO), 2009)
This work was developed with the objective of evaluating the use of trinexapac-ethyl doses (0, 75, 150, 225 and 300 g of the a.i. ha -1) and application times (active tillering, between active tillering and floral differentiation and at floral differentiation) in upland rice crop development and yield. The experiment was carried out in Selvíria-MS, during the agricultural year of 2006/07. Application of 150 g ha -1 of trinexapac-ethyl in Primavera rice cultivar at panicle initiation differentiation reduces plants height, 0.40 m on average comparing to other times, with lodging absence. Trinexapac-ethyl promotes lange number of abnormal grains, reduction of grain yields in doses above 150 g ha -1, when applied in panicle initiation differentiation stadium. Application of 150 g ha -1 of trinexapac-ethyl at any time does not interfere in crop yield.
Use of trinexapac-ethyl growth regulator in upland rice
Keywords: Gibberellin; Oryza sativa L.; Plant growth regulators; Sprinkler irrigation; biochemical composition; crop production; crop yield; cultivar; dose-response relationship; growth regulator; rice; Brazil; Mato Grosso; Mato Grosso do Sul; Primavera do Leste; Selviria; Oryza sativa